The Correlation between Students’ Perception on Zoom during Online Learning and Their Learning Achievement - Auneke Apriyanda Haryati; Weningtyas Parama Iswari; Effendi Limbong (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2022)
This study was conducted to investigate whether there is any significant correlation between students’ perception of using using Zoom during online learning and their learning achievement of the fifth semester students of English Department in Mulawarman University in academic years 2021/2022. The design of this study was quantitative study using correlational method. The researcher took 50 students of fifth semester students of English Department in Mulawarman University in academic years 2021/2022 as the samples. In this study, the researcher used two data in collecting the data. The primary data of this research was questionnaires and the secondary data was students’ GPA from their third to fifth semester. In analyzing the data, the assist of Statistical Package for Social Science (SPSS) was used. The results of computation showed that the rxy of this study was 0.333 or +0.333 which implied there was a positive weak correlation between students’ perceptions of using Zoom during online learning and their learning achievement. The results of hypothesis testing using the p-value showed that Ha was accepted and H0 was rejected due to the judgment criteria if the p-value (0.018) < 0.05, Ha is accepted and H0 is rejected. In conclusion, the results of this study showed there was a significance correlation between students’ perceptions of using zoom during online learning and their learning achievement.